Valorization of wastewater through microalgae as a prospect for generation of biofuel and high-value products. (15th August 2022) - Kumar, Niwas; Banerjee, Chiranjib; Chang, Jo-Shu; Shukla, Pratyoosh
Abstract: Environmental pollution and freshwater crisis are the main pushing forces for upgrading new insights in wastewater treatment. Wastewater generated from different sources is an abundant source of various nutrients; their recovery could be a better perspective to compensate for the demands of the increasing population. Physicochemical or bacterial wastewater treatment processes are inefficient in removing nitrogen (N) and phosphorous (P), are highly energy demanding, and generate secondary sludge. Microalgae offer a better alternative in wastewater treatment because they can consume different inorganic components in wastewater, including nitrogen, phosphorus, and some metals for growth and biomass production. They accomplish pollutants removal coupled with the production of valuable biomass for the generation of bioenergy and commercial products in an eco-friendly manner. The present review focuses on the details of different types of wastewater along with various challenges of microalgal cultivation systems applied in wastewater treatment. The improvements and recent advances in the remediation of wastewater involving microalgae are discussed. Different microalgal growth models and photorespirometry to assess the overall functioning of microalgae in wastewater are also summarized. Furthermore, various industrially important products that can be sustainably obtained from microalgal biomass through wastewater bioremediation are also highlighted. Finally, future perspectives in this field are presented. Graphical abstract: Image 1 Highlights: In-depth insights into wastewaters bioremediation through microalgae are reviewed. Mechanisms involved in the microalgal bioremediation of wastewater are discussed. Challenges and prospects of microalgae-based treatment processes are presented. Such dual benefit techniques serve towards bioremediation and value added products.